Ultra-low thermal conductivity insulation masonry system
Patent Information
- Application Number
- CN202611185273.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明的目的是为了解决传统保温砌块导热系数高、负温环境下砂浆性能劣化、砌体界面热桥显著的问题,而提供了一种超低导保温砌体系统
[0018]本发明砌体系统中,砌块体通过不等高锯齿状凹凸咬合结构进行砌筑,有效阻断了界面热桥,降低了建筑能耗;砌块体通过特殊参数的原料配置而成,其导热系数低,提升了保温性能;研制的负温自适应保温砂浆,在-20℃环境下仍保持高粘接强度,适应严寒地区施工。
Smart Images

Figure CN122899271A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building insulation materials technology, and specifically relates to an ultra-low conductivity thermal insulation masonry system. Background Technology
[0002] In the field of building energy conservation, existing technologies typically employ lightweight insulating blocks (such as aerated concrete blocks) + ordinary cement mortar or early-stage specialized mortar to construct self-insulating walls. However, such existing technologies suffer from the following significant drawbacks: 1) Severe thermal bridging effect in mortar joints: Insulating blocks themselves have low thermal conductivity, but traditional masonry mortar has excessively high thermal conductivity, typically 0.8~1.0 W / (m·K), which is seriously mismatched with the thermal performance of the blocks. This causes horizontal and vertical joints to become the main heat dissipation channels, significantly reducing the overall thermal insulation performance of the wall, making it difficult to meet energy-saving standards in extremely cold regions, and easily causing condensation in the mortar joints.
[0003] 2) Risk of wall cracking and hollowing: Lightweight insulating bricks (such as aerated concrete) have a high water absorption rate, while ordinary mortar has poor water retention. After construction, the mortar dries out too quickly, resulting in insufficient hydration and insufficient bonding strength. This is the main cause of cracking in wall mortar joints, hollowing of the plaster layer, and even leakage.
[0004] 3) Incomplete supporting system: In the existing technology, in order to solve the thermal bridging problem, it is often necessary to use EPS strips embedded in the mortar joints, special masonry methods or secondary insulation treatment, which leads to complex construction procedures, increased costs, and fire or durability hazards, making it difficult to promote on a large scale in conventional projects.
[0005] In view of the above points, there is an urgent need to develop an integrated thermal insulation technology that has low thermal conductivity, strong adaptability to negative temperatures, and can block interfacial thermal bridges. Summary of the Invention
[0006] The purpose of this invention is to solve the problems of high thermal conductivity of traditional thermal insulation blocks, deterioration of mortar performance under negative temperature conditions, and significant thermal bridging at the masonry interface, and to provide an ultra-low thermal conductivity thermal insulation masonry system.
[0007] This invention is achieved through the following technical solution: An ultra-low conductivity thermal insulation masonry system is constructed from several layers of blocks from bottom to top. Each layer of blocks includes several blocks. The front, back, left, and right sides of each block are planar structures, and the top and bottom surfaces of each block are provided with interlocking serrated structures of unequal height. During construction, adjacent blocks in the same layer are bonded together on their left and right sides using negative temperature adaptive thermal insulation mortar, and adjacent blocks in upper and lower layers are bonded together using interlocking structures of their upper and lower surfaces using negative temperature adaptive thermal insulation mortar.
[0008] Negative temperature adaptive thermal insulation mortar is mainly made of cementitious materials, lightweight aggregates, thermal conductivity blocking agents and fiber reinforcing agents. The content of lightweight aggregates accounts for 30% to 50% of the total mass of cementitious materials, the content of thermal conductivity blocking agents accounts for 3% to 5% of the total mass of cementitious materials, and the content of fiber reinforcing agents accounts for 0.8% to 1% of the total mass of cementitious materials.
[0009] Furthermore, multiple protruding ridges are evenly distributed on the top of the block along its length, and multiple grooves are evenly distributed on the bottom of the block along its length. The protruding ridges and grooves fit together, and the height of the grooves is 10mm higher than the height of the protruding ridges.
[0010] Furthermore, the raw materials for preparing negative temperature adaptive thermal insulation mortar also include water-reducing agent and air-entraining agent. The dosage of water-reducing agent is 1.2% of the total mass of cementitious materials, and the dosage of air-entraining agent is 0.05% of the total mass of cementitious materials.
[0011] Furthermore, the cementitious material is prepared from sulfoaluminate cement and fly ash in a mass ratio of 5:5 to 7:3. The lightweight aggregate is modified vitrified microspheres or aerogel particles. The thermal conductivity blocking agent is nano-SiO2-coated phase change capsules. The fiber reinforcing agent is PVA fiber or basalt fiber or a mixture of the two. The water-reducing agent is polycarboxylate water-reducing agent. The air-entraining agent is sodium alkylbenzene sulfonate.
[0012] Furthermore, the bulk density of the modified vitrified microspheres is 80-120 kg / m³. 3 The aerogel particles have a particle size of 50-100μm, the phase change temperature of the nano-SiO2-coated phase change capsules is 25℃, the length of the PVA fiber is 12mm, the length of the basalt fiber is 6mm and the diameter is 15μm, and the solid content of the polycarboxylate superplasticizer is 20%.
[0013] Furthermore, the preparation method of negative temperature adaptive thermal insulation mortar includes the following steps: 1) Weigh the cementitious material, lightweight aggregate, and fiber reinforcing agent according to the proportions, and dry mix until uniformly mixed; 2) Add the thermal conductivity blocker, water-reducing agent and air-entraining agent, mix with the mixing water and pour into the mixer. The water-cement ratio is 0.45. First, mix at low speed for at least 2 minutes, then mix at high speed for at least 1 minute to form a slurry. 3) Measure the initial fluidity of the slurry. If the fluidity is <180mm, adjust the water-reducing agent dosage by ±0.2% until the fluidity of the slurry is ≥180mm.
[0014] Furthermore, the joint thickness of the negative temperature adaptive thermal insulation mortar is ≤5mm, the fluidity is ≥180mm, the bond strength after freeze-thaw at -20℃ is ≥0.5Mpa, and the thermal conductivity is ≤0.08W / (m·K).
[0015] Furthermore, the blocks are mainly made of the following raw materials in parts by weight: 40-50 parts by weight of cementitious material, 35-45 parts by weight of lightweight aggregate, 3-5 parts by weight of thermal conductivity blocking agent, and 0.8-1.2 parts by weight of fiber reinforcing agent.
[0016] Furthermore, the cementitious material is a mixture of sulfoaluminate cement and fly ash in a mass ratio of 6:4, the lightweight aggregate is modified vitrified microspheres, the thermal conductivity blocking agent is nano-SiO2-coated phase change capsules, and the fiber reinforcing agent is PVA fiber.
[0017] Furthermore, the method for preparing the blocks includes the following steps: 1) Mix the cementitious materials, lightweight aggregates, thermally insulating agents and fiber reinforcing agents according to the specified ratio, add water and stir to form a slurry with a water-cement ratio of 0.45; 2) Pour the slurry into the mold, and then place the mold in a temperature-controlled curing oven and cure for 7 days under conditions of humidity ≥95% and temperature gradient 20℃-30℃. 3) The thermal conductivity of the prepared blocks is 0.06 W / (m·K), and the compressive strength is ≥3.5 MPa.
[0018] In the masonry system of this invention, the masonry blocks are laid by a sawtooth interlocking structure with unequal heights, which effectively blocks the interface thermal bridge and reduces building energy consumption. The masonry blocks are made of raw materials with special parameters, which have low thermal conductivity and improve thermal insulation performance. The developed negative temperature adaptive thermal insulation mortar still maintains high bonding strength in an environment of -20℃, making it suitable for construction in extremely cold regions. Attached Figure Description
[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments of the present invention will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a three-dimensional structural diagram of the block in this invention.
[0021] Figure 2 This is a schematic diagram of the overall structure of the ultra-low conductivity thermal insulation masonry system made of masonry blocks in this invention.
[0022] In the diagram: 1-block; 1-1-protruding edge, 1-2-groove. Detailed Implementation
[0023] The embodiments of the technical solution of the present invention will now be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore merely examples and should not be used to limit the scope of protection of the present invention. It should be noted that, unless otherwise stated, the technical or scientific terms used in this application should have the ordinary meaning understood by those skilled in the art to which this invention pertains. Example 1
[0024] like Figure 1 and Figure 2 As shown, this embodiment provides an ultra-low conductivity thermal insulation masonry system, which is constructed from several layers of blocks from bottom to top, and each layer of blocks includes several block bodies 1.
[0025] The front, back, left, and right sides of the block 1 are all planar structures. The top and bottom surfaces of the block 1 are provided with serrated interlocking structures of unequal height. Specifically, multiple protruding ridges 1-1 are evenly distributed along the length of the top surface of the block 1, and multiple grooves 1-2 are evenly distributed along the length of the bottom surface of the block 1. The protruding ridges 1-1 and the grooves 1-2 are interlocked and matched, and the height of the grooves 1-2 is 10mm higher than the height of the protruding ridges 1-1.
[0026] During construction, adjacent blocks 1 in the same layer are bonded together on their left and right sides using negative temperature adaptive thermal insulation mortar, and adjacent blocks 1 in upper and lower layers are bonded together on their upper and lower surfaces using negative temperature adaptive thermal insulation mortar.
[0027] Block 1 is mainly composed of 40-50 parts by weight of cementitious material, 35-45 parts by weight of lightweight aggregate, 3-5 parts by weight of thermally insulating agent, and 0.8-1.2 parts by weight of fiber reinforcing agent; wherein, the cementitious material is a mixture of sulfoaluminate cement and fly ash in a mass ratio of 6:4; the lightweight aggregate is modified vitrified microspheres, and the bulk density of the modified vitrified microspheres is 80-120 kg / m³. 3 The thermal conductivity blocking agent uses nano-SiO2-coated phase change capsules, and the phase change temperature of the nano-SiO2-coated phase change capsules is 25℃; the fiber reinforcing agent uses PVA fiber, and the length of the PVA fiber is 12mm.
[0028] Negative-temperature adaptive thermal insulation mortar is mainly composed of cementitious materials, lightweight aggregates, thermally conductive blocking agents, fiber reinforcing agents, water-reducing agents, and air-entraining agents. Among them, the content of lightweight aggregates accounts for 30% to 50% of the total mass of cementitious materials, the content of thermally conductive blocking agents accounts for 3% to 5% of the total mass of cementitious materials, the content of fiber reinforcing agents accounts for 0.8% to 1% of the total mass of cementitious materials, the content of water-reducing agents accounts for 1.2% of the total mass of cementitious materials, and the content of air-entraining agents accounts for 0.05% of the total mass of cementitious materials.
[0029] In negative temperature adaptive thermal insulation mortar, the cementitious material is prepared by mixing sulfoaluminate cement and fly ash in a mass ratio of 5:5 to 7:3. 42.5 grade sulfoaluminate cement is preferred, and Grade I fly ash is preferred. The lightweight aggregate consists of modified vitrified microspheres or aerogel particles, with the bulk density of the modified vitrified microspheres being 80-120 kg / m³. 3 The aerogel particles have a particle size of 50-100μm; the thermally conductive blocking agent is a phase change capsule coated with nano-SiO2, and the phase change temperature of the nano-SiO2-coated phase change capsule is 25℃; the fiber reinforcing agent is PVA fiber or basalt fiber or a mixture of the two, with the PVA fiber having a length of 12mm and the basalt fiber having a length of 6mm and a diameter of 15μm. When a mixture of the two is used, the mixing mass ratio of PVA fiber or basalt fiber is 1:1; the water-reducing agent is a polycarboxylate water-reducing agent with a solid content of 20%; the air-entraining agent is sodium alkylbenzene sulfonate. Example 2
[0030] This embodiment provides a method for preparing the negative temperature adaptive thermal insulation mortar described in Embodiment 1, specifically including the following steps: 1) Weigh the cementitious material, lightweight aggregate and fiber reinforcing agent according to the proportions described in Example 1, and dry mix until uniform.
[0031] 2) Add the heat-conducting inhibitor, water-reducing agent and air-entraining agent, mix with the mixing water and pour into the mixer. The water-cement ratio is 0.45 (the ratio of the mass of the mixing water to the total mass of the cementitious material). First, stir at low speed for at least 2 minutes, then stir at high speed for at least 1 minute to form a slurry.
[0032] For the proportions of each raw material in steps 1) and 2) above, the following proportions can be selected: "Sulfoaluminate cement and fly ash mass ratio 5:5, lightweight aggregate content 50%, fiber reinforcing agent content 1.0% (basalt 0.5% + PVA 0.5%), thermal conductivity blocking agent content 5%, water reducing agent content 1.2%, air entraining agent content 0.05%" or "Sulfoaluminate cement and fly ash mass ratio 6:4, lightweight aggregate content 40%, fiber reinforcing agent content 1.0% (PVA), thermal conductivity blocking agent content 4%, water reducing agent content 1.2%, air entraining agent content 0.05%" or "Sulfoaluminate cement and fly ash mass ratio 7:3, lightweight aggregate content 30%, fiber reinforcing agent content 0.8% (basalt), thermal conductivity blocking agent content 3%, water reducing agent content 1.2%, air entraining agent content 0.05%".
[0033] 3) Measure the initial fluidity of the slurry. If the fluidity is <180mm, adjust the water-reducing agent dosage by ±0.2% until the fluidity of the slurry is ≥180mm.
[0034] The prepared negative temperature adaptive thermal insulation mortar has a joint thickness of ≤5mm, a fluidity of ≥180mm, a bond strength of ≥0.5MPa after freeze-thaw at -20℃, and a thermal conductivity of ≤0.08W / (m·K). Example 3
[0035] This embodiment provides a method for preparing the block 1 described in Embodiment 1, specifically including the following steps: 1) Mix the cementitious material, lightweight aggregate thermal conductivity blocker and fiber reinforcing agent according to the proportions described in Example 1, add water and stir to form a slurry, with a water-cement ratio of 0.45 (the ratio of the mass of mixing water to the total mass of cementitious material).
[0036] For the proportions of each raw material in step 1) above, the following proportions can be selected: "40 parts by weight of cementitious material, 45 parts by weight of lightweight aggregate, 4 parts by weight of thermal conductivity blocking agent, and 0.8 parts by weight of fiber reinforcing agent" or "50 parts by weight of cementitious material, 35 parts by weight of lightweight aggregate, 3 parts by weight of thermal conductivity blocking agent, and 1.2 parts by weight of fiber reinforcing agent" or "45 parts by weight of cementitious material, 40 parts by weight of lightweight aggregate, 5 parts by weight of thermal conductivity blocking agent, and 1.0 part by weight of fiber reinforcing agent".
[0037] 2) Inject the slurry into the mold, and then place the mold in a temperature-controlled curing oven and cure for 7 days under conditions of humidity ≥95% and temperature gradient 20℃-30℃.
[0038] The prepared block 1 has a thermal conductivity of 0.06 W / (m·K) and a compressive strength ≥3.5 MPa. Example 4
[0039] Further detailed implementation and corresponding performance analysis of the negative temperature adaptive thermal insulation mortar described in Examples 1 and 2 are provided below: 1) Raw materials and equipment (1) Raw materials Cementing materials: sulfoaluminate cement (grade 42.5), grade I fly ash.
[0040] Lightweight aggregates: modified vitrified microspheres (bulk density 80-120 kg / m³), aerogel particles (particle size 50-100 μm).
[0041] Functional additives: Thermal conductivity blocking agent: Nano-SiO2 coated phase change capsules (phase change temperature 25℃).
[0042] Fiber reinforcing agents: basalt fiber (6mm in length, 15μm in diameter), PVA fiber (12mm in length).
[0043] Additives: Polycarboxylate superplasticizer (20% solid content), air-entraining agent (sodium alkylbenzene sulfonate).
[0044] Mixing water: Deionized water.
[0045] (2) Equipment Planetary cement mixer (JJ-5 type), flow table (ISO standard); Thermal conductivity meter (Hot Disk TPS 2500S); Universal testing machine (300kN, with low temperature environment chamber); Freeze-thaw cycle test chamber (-30℃~50℃).
[0046] 2) Implementation Design (1) Factors and levels in orthogonal experiments Four key influencing factors were selected, with three levels for each factor, using the L9(3) method. 4 The experiments were arranged using an orthogonal array (Table 1).
[0047] Table 1. Factors and levels in orthogonal experiments
[0048] (2) Basic proportions (fixed parameters) Water-to-binder ratio: 0.45 (determined based on preliminary flowability experiments); Water-reducing agent dosage: 1.2% (as a percentage of the total cementitious material content); Air-entraining agent dosage: 0.05% (as a percentage of the total cementitious material).
[0049] 3) Implementation steps (1) Mortar preparation 1. Weigh out the sulfoaluminate cement, Grade I fly ash, lightweight aggregate, and fiber reinforcing agent according to the proportion, and dry mix for 30 seconds until uniformly mixed; 2. Add thermal conductivity blocking agent, polycarboxylate superplasticizer, and air-entraining agent, mix with mixing water, pour into a mixer, stir at low speed for 2 minutes, and then stir at high speed for 1 minute; 3. Measure the initial flowability. If the flowability is <180mm, adjust the water-reducing agent dosage appropriately (±0.2%).
[0050] (2) Specimen molding and curing Bond strength test specimens: Figure-eight molds (40mm×40mm×160mm) were used, with 3 specimens per group. The specimens were demolded 24 hours after molding and cured under standard conditions (20℃±2℃, humidity≥95%) for 7 days. Thermal conductivity test specimen: Φ100mm×50mm cylindrical mold, tested after 28 days of curing; Freeze-thaw cycle specimens: Same as the bond strength specimens, after curing for 28 days, undergo freeze-thaw cycles at -20℃ (each cycle: freeze for 4 hours → thaw for 4 hours, for a total of 50 cycles).
[0051] Performance testing methods Flowability: Determined according to GB / T 2419-2005 "Determination of Flowability of Cement Mortar"; Thermal conductivity: Hot Disk thermal constant analyzer, using the transient plane heat source method (TPSS); Bond strength: universal testing machine, tensile rate 0.5 mm / min, tested before and after freeze-thaw. Gas content: Gas content was determined using a volumetric gas content analyzer (GB / T17431.2-2019).
[0052] 4) Data processing and optimization 1. Intuitive Analysis: Calculate the average performance index of each factor at different levels to determine the optimal combination of levels; 2. Analysis of variance: Determine the significance of each factor on performance (significance level α=0.05); 3. Verification experiment: Conduct three repeated experiments on the optimal ratio to verify the performance stability; 4. Microstructure analysis: Fiber dispersion, pore distribution and interfacial transition zone characteristics were observed using SEM.
[0053] 5) Results of orthogonal experiments 1. Orthogonal Experiment Data Recording Table (using L9(3)) 4 (Orthogonal array, experiment repeated 3 times, results are taken as mean ± standard deviation)
[0054] 2. Visual analysis results (range R-value)
[0055] 3. Optimal proportion verification experimental data (based on comprehensive performance screening of A2B3C3D3 combination: cementitious material 6:4, lightweight aggregate 50%, thermal conductivity blocking agent 5%, mixed fiber reinforcing agent)
[0056] 4. Conclusion a. The amount of lightweight aggregate (B) has the most significant effect on thermal conductivity (range 0.018), and a 50% addition can reduce thermal conductivity by 19.6%; b. The blended fiber reinforcement (D3) showed the best performance in improving bond strength (+6.8%) and reducing freeze-thaw degradation (-3.1%); c. The optimal ratio (A2B3C3D3) has the best overall performance and can be used as the preferred production benchmark formula.
[0057] Data Description: All tests were performed in accordance with GB / T25181-2019 "Premixed Mortar" and the methods in the scheme, with a standard deviation of ≤5%.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.
Claims
1. An ultra-low conductivity thermal insulation masonry system, characterized in that: It is constructed from several layers of blocks from bottom to top, with each layer consisting of several blocks. The front, back, left, and right sides of each block are planar structures, and the top and bottom surfaces of each block have interlocking serrated structures of varying heights. During construction, adjacent blocks in the same layer are bonded together on their left and right sides using negative temperature adaptive thermal insulation mortar, while adjacent blocks in upper and lower layers have interlocking structures on their top and bottom surfaces using negative temperature adaptive thermal insulation mortar. Negative temperature adaptive thermal insulation mortar is mainly made of cementitious materials, lightweight aggregates, thermal conductivity blocking agents and fiber reinforcing agents. The content of lightweight aggregates accounts for 30% to 50% of the total mass of cementitious materials, the content of thermal conductivity blocking agents accounts for 3% to 5% of the total mass of cementitious materials, and the content of fiber reinforcing agents accounts for 0.8% to 1% of the total mass of cementitious materials.
2. The ultra-low conductivity thermal insulation masonry system according to claim 1, characterized in that: The block has multiple raised edges evenly distributed along its length on its top surface and multiple grooves evenly distributed along its bottom surface. The raised edges and grooves fit together, and the height of the grooves is 10mm higher than the height of the raised edges.
3. The ultra-low conductivity thermal insulation masonry system according to claim 2, characterized in that: The raw materials for preparing negative temperature adaptive thermal insulation mortar also include water-reducing agent and air-entraining agent. The amount of water-reducing agent is 1.2% of the total mass of cementitious materials, and the amount of air-entraining agent is 0.05% of the total mass of cementitious materials.
4. The ultra-low conductivity thermal insulation masonry system according to claim 3, characterized in that: The cementitious material is made of sulfoaluminate cement and fly ash in a mass ratio of 5:5 to 7:
3. The lightweight aggregate is modified vitrified microspheres or aerogel particles. The thermal conductivity blocking agent is nano-SiO2-coated phase change capsules. The fiber reinforcing agent is PVA fiber or basalt fiber or a mixture of the two. The water-reducing agent is polycarboxylate water-reducing agent. The air-entraining agent is sodium alkylbenzene sulfonate.
5. The ultra-low conductivity thermal insulation masonry system according to claim 4, characterized in that: The bulk density of the modified vitrified microspheres is 80-120 kg / m³. 3 The aerogel particles have a particle size of 50-100μm, the phase change temperature of the nano-SiO2-coated phase change capsules is 25℃, the length of the PVA fiber is 12mm, the length of the basalt fiber is 6mm and the diameter is 15μm, and the solid content of the polycarboxylate superplasticizer is 20%.
6. The ultra-low conductivity thermal insulation masonry system according to claim 5, characterized in that, The preparation method of negative temperature adaptive thermal insulation mortar includes the following steps: 1) Weigh the cementitious material, lightweight aggregate, and fiber reinforcing agent according to the proportions, and dry mix until uniformly mixed; 2) Add the thermal conductivity blocker, water-reducing agent and air-entraining agent, mix with the mixing water and pour into the mixer. The water-cement ratio is 0.
45. First, mix at low speed for at least 2 minutes, then mix at high speed for at least 1 minute to form a slurry. 3) Measure the initial fluidity of the slurry. If the fluidity is <180mm, adjust the water-reducing agent dosage by ±0.2% until the fluidity of the slurry is ≥180mm.
7. The ultra-low conductivity thermal insulation masonry system according to claim 6, characterized in that: The joint thickness of the negative temperature adaptive thermal insulation mortar is ≤5mm, the fluidity is ≥180mm, the bond strength after freeze-thaw at -20℃ is ≥0.5Mpa, and the thermal conductivity is ≤0.08W / (m·K).
8. The ultra-low conductivity thermal insulation masonry system according to claim 1, characterized in that, The blocks are mainly made of the following raw materials in parts by weight: 40-50 parts cementitious material, 35-45 parts lightweight aggregate, 3-5 parts thermal conductivity blocker, and 0.8-1.2 parts fiber reinforcing agent.
9. The ultra-low conductivity thermal insulation masonry system according to claim 8, characterized in that: The cementitious material is a mixture of sulfoaluminate cement and fly ash in a mass ratio of 6:
4. The lightweight aggregate is modified vitrified microspheres, the thermal conductivity blocking agent is nano-SiO2-coated phase change capsules, and the fiber reinforcement is PVA fiber.
10. The ultra-low conductivity thermal insulation masonry system according to claim 8 or 9, characterized in that, The preparation method of the blocks includes the following steps: 1) Mix the cementitious materials, lightweight aggregates, thermally insulating agents and fiber reinforcing agents according to the specified ratio, add water and stir to form a slurry with a water-cement ratio of 0.45; 2) Pour the slurry into the mold, and then place the mold in a temperature-controlled curing oven and cure for 7 days under conditions of humidity ≥95% and temperature gradient 20℃-30℃. 3) The thermal conductivity of the prepared blocks is 0.06 W / (m·K), and the compressive strength is ≥3.5 MPa.